1976
DOI: 10.1111/j.1600-051x.1976.tb01847.x
|View full text |Cite
|
Sign up to set email alerts
|

Bone morphology and bone loss in periodontal disease

Abstract: A clinical study of the distribution of different types of bone defects in chronic periodontitis was carried out on 30 patients. An analysis of 176 defects suggests that their distribution reflects the original morphology of the alveolar bone. The role of function as a determinant of that morphology is examined. While there appears to be a relationship between functional stress and the phylogenesis of the bone, there is no direct relationship between function and ontogenesis. A study of growth remodelling of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
1

Year Published

1981
1981
2020
2020

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(23 citation statements)
references
References 24 publications
1
21
1
Order By: Relevance
“…Several cross-sectional studies have demonstrated decreased bone mass and density (Kribbs, 1990;Moshchil' etal, 1991), as well as reduced bone mineral content (von Wopwern, 1988) in edentulous mandibles of postmenopausal females. A variety of studies have attempted to provide insight into the relationship of osteoporosis to periodontitis, but the results of these studies have been equivocal (Groen et al, 1968;Phillips and Ashley, 1973;Ward and Manson, 1973;Manson, 1976;Baum, 1981;Daniell, 1983;Kribbs, 1990). To ascertain if osteoporosis is a risk factor for periodontal attachment loss in postmenopausal women, well-designed, long-term longitudinal investigations controlling for temporal period following the menopause, plaque levels, medications used (e.g., hormones, etc.…”
Section: Menopausementioning
confidence: 99%
“…Several cross-sectional studies have demonstrated decreased bone mass and density (Kribbs, 1990;Moshchil' etal, 1991), as well as reduced bone mineral content (von Wopwern, 1988) in edentulous mandibles of postmenopausal females. A variety of studies have attempted to provide insight into the relationship of osteoporosis to periodontitis, but the results of these studies have been equivocal (Groen et al, 1968;Phillips and Ashley, 1973;Ward and Manson, 1973;Manson, 1976;Baum, 1981;Daniell, 1983;Kribbs, 1990). To ascertain if osteoporosis is a risk factor for periodontal attachment loss in postmenopausal women, well-designed, long-term longitudinal investigations controlling for temporal period following the menopause, plaque levels, medications used (e.g., hormones, etc.…”
Section: Menopausementioning
confidence: 99%
“…Alveolar crest bone loss may occur throughout life as a consequence of chronic inflammatory periodontal disease, resulting in root exposure and gingival recession (Manson, 1976). The distance from the cement enamel junction (CEJ) to alveolar crest (AC) has been widely used in order to measure the degree of alveolar bone loss.…”
Section: Introductionmentioning
confidence: 99%
“…(3.4.4) Periodontal disease Several workers have found a weak, sometimes indirect, correlation between skeletal bone status and periodontal disease (Phillips and Ashley, 1973;Manson, 1976;von Wowern et al, 1994). For example, patients who had suffered an osteoporotic fracture were found to have 0.8 mm more attachment loss per site (von Wowern et al, 1994), a small difference to be detected clinically.…”
Section: (33) Gendermentioning
confidence: 99%